1993
DOI: 10.1136/adc.68.5.632
|View full text |Cite
|
Sign up to set email alerts
|

Functional significance of dystrophin positive fibres in Duchenne muscular dystrophy.

Abstract: The age when boys lose the ability to walk independently is one of the milestones in the progression of Duchenne (usually <1%) or very weak labelling on a much higher proportion (about 25%). The mean age at loss of mobility among the DMD patients with no dystrophin labelling on tissue sections was 7 9 years (range 63-9 5) while the mean age among those with some labelling was 9'9 years (range 8*0-11-9); this is a significant difference. Quantitative estimates of dystrophin abundance were obtained from den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
30
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 29 publications
0
30
0
Order By: Relevance
“…Over twenty years ago, low-level dystrophin expression in DMD patient muscle was reported [12][13][14], and Nicholson and colleagues hypothesized that dystrophin in DMD muscle could result from exon skipping [12]. Gangopadhyay et al [13] found up to 10-12% of normal dystrophin levels in DMD patients with deletions of exons 3-7, but no evidence of framerestoring exon skipping.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Over twenty years ago, low-level dystrophin expression in DMD patient muscle was reported [12][13][14], and Nicholson and colleagues hypothesized that dystrophin in DMD muscle could result from exon skipping [12]. Gangopadhyay et al [13] found up to 10-12% of normal dystrophin levels in DMD patients with deletions of exons 3-7, but no evidence of framerestoring exon skipping.…”
mentioning
confidence: 99%
“…However, the validity of such markers as surrogate indicators of dystrophin presence and functionality, and their utility in evaluating emerging therapies for DMD is unproven. Furthermore, the ability of surrogate biomarkers to discriminate therapy-mediated benefits from those due to variable (low) levels of endogenous dystrophin, frequently detected in DMD muscle [12,36], remains questionable at this time.…”
mentioning
confidence: 99%
See 3 more Smart Citations